Online Arbitration for the Settlement of Disputes in the Contracts of Electronic Commerce - Alseadoon, Renad Abdulkarim Mohammed; Alseadoon, Abdulkarim Mohammad Abdulkarim; Abdulwhab, Mohammad Abdastar (Journal of Economic, Administrative and Legal Sciences, 2023)
This study aims to clarify the best and most appropriate alternative means for settling disputes of e-commerce contracts and clarify their nature, and the effect of adding the electronic arbitration clause on electronic contracts. Their nature exceeds the spatial and temporal limits in contracting, by following the descriptive approach in clarifying the systemic facts and merging it with the analytical approach to understand the nature, advantages and disadvantages of electronic arbitration in the settlement of disputes of e-commerce contracts according to scientific foundations.This study consists of an introduction and two chapters. The introduction contains the research problem, its objectives, the importance of previous studies that have been exposed to this field, the research methodology, and finally the research plan. After that, a preamble section is added to clarify the definition of e-commerce and numerical data indicating its importance. The first chapter is entitled e-commerce and the laws that govern it which is divided into three branches. The first, is the nature of the electronic contract. The second, is the international laws of electronic commerce. The third, is the applicable law. The second chapter came under the title of electronic arbitration which is also, divided into three branches. The first, is the nature of arbitration. The second, is the nature of electronic arbitration. The third, is the electronic arbitration ruling. Finally, the conclusion, the recommendations were formulated with the aim of trying to find several solutions and improvements in the field of settling disputes of e-commerce contracts, by paying attention to the development of awareness of the impact of arbitration in settling disputes of e-commerce contracts and its advantages, and seeking in practice to settle disputes of e-commerce contracts through electronic arbitration.
Keywords: Arbitration; online; settlement; contract; electronic commerce